Projected number of osteoarthritis patients in Austria for the next decades – quantifying the necessity of treatment and prevention strategies in Europe - Wolfgang Hitzl; Tanja Stamm; Margreet Kloppenburg; Markus Ritter; Martin Gaisberger; Antje van der Zee-Neuen (BMC Musculoskeletal Disorders, 2022)
Abstract Background The present study aimed to predict the expected number of patients with osteoarthritis (OA) in Austria up to the year 2080. Methods Demographic data and population projections between 2019 and 2080 were obtained from European authorities. Information about recent age- and sex-stratified prevalence of patients with self-reported physician-diagnosed OA was obtained from the Austrian Health Interview Survey (n = 15,771). Projections were stratified by age and sex; sensitivity analyses were performed based on aging, main (most likely), and growth scenarios of the population. Results Based on the projection, the overall increase in the total number of patients with OA from 2019 to 2080 will be 38% for men and women. In 2019, the highest number of OA-patients nested in the groups of persons aged 70-79 (n = 238,749) and 60-69 (n = 237,729) years. In 2080, the 80+ age group is predicted to have the highest number of OA with 421,548 individuals (i.e. factor 3.45 and factor 2.48 increase in the male and female group, respectively, compared to 2019), followed by the group aged 70-79 with 314,617 individuals (factor 1.45 and factor 1.28 increase in the male and female group, respectively, compared to 2019). Similar trends were found in the ageing and growing scenarios. Conclusions The projected increase in the occurrence of OA will likely lead to a substantial socioeconomic burden for the Austrian healthcare system in the near and far future. The current findings plead for the development of sustainable concepts for the treatment and prevention of OA by European authorities.